2017
DOI: 10.1002/ps.4730
|View full text |Cite
|
Sign up to set email alerts
|

Early flowering and rapid grain filling determine early maturity and escape from harvesting in weedy rice

Abstract: Early maturity is an essential factor determining the persistence of weedy rice by contributing to the escape of its seed from being harvested with the rice crop. Both early flowering and shorter grain-filling stages determine early maturity, and flowering is more plastic than grain filling. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 45 publications
1
34
0
Order By: Relevance
“…Panicle length (cm) 10 Awn length (cm) 11 Grain length (mm) 12 Grain width (mm) 13 Culm diameter (cm) 14 Tillage practice 15…”
Section: Phenotypic Diversity and Agroecological Effects In Arkansas mentioning
confidence: 99%
See 2 more Smart Citations
“…Panicle length (cm) 10 Awn length (cm) 11 Grain length (mm) 12 Grain width (mm) 13 Culm diameter (cm) 14 Tillage practice 15…”
Section: Phenotypic Diversity and Agroecological Effects In Arkansas mentioning
confidence: 99%
“…Being conspecific with cultivated rice makes control of weedy rice difficult because morphological and physiological traits are shared with the crop. Some weeds successfully outcompete the crop or escape management or removal at harvest; for example, enhanced photosynthesis of weedy rice at the seedling stage, early flowering and rapid grain filling determine early maturity and allow competitive dominance of weedy genotypes over cultivated rice . Other weeds adapt to a managed ecosystem with consistent artificial selection through phenotypic mimicry of the cultivated plant .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It competes for nutrients, water, sunlight and other resources with cultivated rice and consequently affects crop production [3,4]. Thus, for example, in China, weedy rice can reduce rice crop yield by 10 % -50 %, and consequently cause serious economic loss [5]. Furthermore, it has many morphological and physiological traits related to weediness, and is strongly characterized by its high seed shattering rate [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In agro-ecosystems, many forms of human activity can contribute to weed dispersal; weed seeds can be spread with manure used as fertilizer (Dastgheib 1989;Pleasant and Schlather 1994), irrigation water (Dastgheib 1989), and by machinery during soil tillage and harvesting operations (Wiles and Brodahlb 2004). Weedy rice normally disperses its seed by gravity under non disturbed conditions in absence of particular dispersal structures in the seed and by having a relatively large mass (Zhao et al 2017); the wide-range and long-distance dispersal of weedy rice seed by water, wind, and animals is also limited. Previous studies indicated that weed species such as Panicum miliaceum (Mccanny and Cavers 1988), Lolium rigidum (Blanco-Moreno et al 2003), and Avena fatua (Shirtliffe and Entz 2005) could be dispersed widely within a field by combine harvesters during harvesting.…”
Section: Introductionmentioning
confidence: 99%